Brand Image and Customer Loyalty: Exploring the Power of Word of Mouth - Nhinh Thi Tran; Le Hang Thi Nguyen (Emerging Science Journal, 2026)
This study aims to examine the moderating role of word of mouth (WOM) in the relationship between brand image and customer loyalty within the Vietnamese market context. While previous research has primarily explored WOM as a direct influencing factor, limited attention has been given to its moderating effect on this specific relationship. Employing a quantitative research design, the study collected data through a structured survey, distributing 950 questionnaires and obtaining 829 valid responses. The data were analyzed using PLS-SEM via SmartPLS 4.0 software. The findings indicate that WOM significantly moderates the relationship between brand image and customer loyalty, such that positive WOM reinforces consumer loyalty when brand perceptions are favorable, particularly when the message comes from influential sources such as celebrities or opinion leaders. Conversely, negative WOM can attenuate the effects of brand image and result in decreased loyalty. The study contributes to the existing literature by clarifying the contextual influence of WOM in a collectivist culture and offering practical implications for marketers in developing communication strategies that leverage WOM to enhance brand equity and customer retention. This research provides novel empirical evidence relevant to both theory development and managerial practice in emerging markets. JEL Classification: M30, M31, O35.